Strategic design to ensure the sustainable productivity of military division government organization - Sari, Rini Mulyani; Nugraha, Evan (Edelweiss Applied Science and Technology, 2024)
This study aims to analyze the impact of the balanced scorecard and good corporate governance on the productivity of military government organizations and develop strategies to ensure their sustainability. This research implements a mixed-methods strategy utilizing a sequential explanatory research plan. This process is followed by a Mapping strategy, culminating in the presentation of conclusions. One hundred individuals who worked in military government agencies were surveyed as part of this study. This analysis comprises quantitative and qualitative data collected from 100 personnel of the government agency within the military division. This study determined that the environment is the primary factor in guaranteeing the long-term productivity sustainability of government organizations within military divisions. The implication is that leaders need to conduct in-depth research and be aware of environmental changes, both internal and external, that occur in military departmental government organizations.